2020
DOI: 10.1111/jgs.16638
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Sex‐Specific Physical Function Trends by Age, Race/Ethnicity, and Weight Status

Abstract: BACKGROUND: There is a need to assess longitudinal trends in physical function and to understand the prevalence of physical function status in the older population using objectively measured physical function. Therefore, the primary purpose of this study was to examine longitudinal sex-specific physical function trends and prevalence of physical function status by age, race/ethnicity, and weight status in older adults, aged 65 years and older. METHODS: The present study used longitudinal data from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(95 reference statements)
1
11
0
1
Order By: Relevance
“…The range of SPPB scores in this sample of women would be considered 'fair' 19 .A recent systematic review and meta-analysis 20 confirmed that SPPB scores of 7-9 and 4-6 were associated with an increased risk of all-cause mortality (OR=1.5 and 2.41, respectively) compared to scores of 10-12. Grip strength < 20 kg in women was recently shown to be highly predictive of mobility limitations in older women 21 as well as overall muscle weakness and predictor of sarcopenia.…”
Section: Discussionmentioning
confidence: 71%
“…The range of SPPB scores in this sample of women would be considered 'fair' 19 .A recent systematic review and meta-analysis 20 confirmed that SPPB scores of 7-9 and 4-6 were associated with an increased risk of all-cause mortality (OR=1.5 and 2.41, respectively) compared to scores of 10-12. Grip strength < 20 kg in women was recently shown to be highly predictive of mobility limitations in older women 21 as well as overall muscle weakness and predictor of sarcopenia.…”
Section: Discussionmentioning
confidence: 71%
“…According to previous studies, we found that some population characteristics (e.g., age, sex, ethnicity, and so on) (34)(35)(36)(37)(38)(39) and lifestyles (e.g., currently smoking, current consuming alcohol, and regular exercise) (40)(41)(42)(43) may confound the associations between serum albumin and physical functioning. Thus, as done in the previous study based on CLHLS (44), the following covariates were included in our analysis: age, sex, residence (rural vs. other), ethnicity (Han vs. other), education (≥1 year of education vs. no education), economic independence (yes vs. no), lifetime primary occupation (white-collar occupation vs. others), and being in receipt of adequate medications (yes vs. no); co-residence with children (yes vs. no) and current marital status (married vs. others) were used to assess participants' social support and contact; lifestyle consisted of consuming alcohol (yes vs. no), currently smoking (yes vs. no), and regular exercise (yes vs. no).…”
Section: Covariatesmentioning
confidence: 82%
“…We performed GEE models to assess temporal trends in the prevalence of vision impairment by examining higher-order terms of survey year [18]. The presence of vision impairment was modelled as a binomial outcome with a logit link in GEE models, with an exchangeable working correlation to account for repeated visual assessments of the same participant.…”
Section: Statistical Analysesmentioning
confidence: 99%